1995
DOI: 10.1016/s0741-5214(95)70046-3
|View full text |Cite
|
Sign up to set email alerts
|

Venous hemodynamics during impulse foot pumping

Abstract: Intermittent pneumatic compression of the plantar venous plexus produces measurable increases in venous outflow from the lower limbs of normal subjects. This study seems to justify further evaluation of the effectiveness of this technique for mechanical deep venous thrombosis prophylaxis in selected high-risk patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…This inevitably means that patient compliance can be more of a problem with foot compression, 29 although the proper use of intermittent compression in a hospital situation will depend on many other factors, such as staff training. 30,31 There is good recent evidence that foot compression is hemodynamically effective, [13][14][15][16][17][18][19][32][33][34] typically showing doubling of peak velocities on compression compared with resting, with some small differences between systems. 13 Comparison with calf and/or thigh compression depends, as previously discussed, on the definition of a "good" response.…”
Section: Is Foot Compression As Effective As Calf Compression?mentioning
confidence: 99%
“…This inevitably means that patient compliance can be more of a problem with foot compression, 29 although the proper use of intermittent compression in a hospital situation will depend on many other factors, such as staff training. 30,31 There is good recent evidence that foot compression is hemodynamically effective, [13][14][15][16][17][18][19][32][33][34] typically showing doubling of peak velocities on compression compared with resting, with some small differences between systems. 13 Comparison with calf and/or thigh compression depends, as previously discussed, on the definition of a "good" response.…”
Section: Is Foot Compression As Effective As Calf Compression?mentioning
confidence: 99%
“…I Orthip &A, Vol. 17, No. 1, 1999 prcssion of the legs, which has been shown to more effectively empty the vessels and return blood to the heart, (b) more comfort during application because of the lower pressure, (c) higher venous velocity (22), and (d) faster inflation.…”
Section: Application Of the Intermittent Pneumatic-compression Devicementioning
confidence: 99%
“…Studies have suggested that this mechanical method effectively reduces the incidence of deep vein thrombosis without side effects by preventing stasis in the venous system through an increase in venous blood flow (13,17) and by elevating fibrinolytic activity (16,28).…”
mentioning
confidence: 99%
“…Since it was first introduced into clinical use in 1972 (Hills et al, 1972), IPC has been widely used clinically as an effective means of preventing the development of DVT and PE (Clagett and Reisch, 1988;Woolson and Watt, 1991;Pidala et al, 1992;Woolson, 1996) and has been shown to reduce the incidence of DVT from 29-53% in patients treated with pharmacological agents to 17% in patients treated with IPC (Westrich et al, 2000). Studies have suggested that this mechanical method effectively reduces the incidence of DVT without side effects by preventing stasis in the venous system through an increase in venous blood flow (Janssen et al, 1993;Killewich et al, 1995;Malone et al, 1999) and by elevating fibrinolytic activity Kessler et al, 1996).…”
Section: Introductionmentioning
confidence: 99%